The statistical characteristics of a superhet retransmitting meter signal - Величко, Анатолий Федорович; Величко, Дмитрий Анатольевич; Величко, Сергей Анатольевич; Вичкань, Алексей Валерьевич; Клюева, Анна Николаевна; Нетребенко, Константин Владимирович (Eastern-European Journal of Enterprise Technologies, 2015)
Using computer simulation, distribution densities of the signal phases and amplitudes of superhet measuring retransmitting systems (MRS) and radar sensors were obtained. The features and relations of such signal characteristics of MRS and radar sensors to random effects on the stable controlled object were obtained, the results of their comparative analysis were given. The effect of fluctuating reflectors on the statistical signal characteristics of the MRS currently has hardly been studied, but has been well studied for the case of radar sensors. Therefore, it is necessary to take into account the peculiarities of these effects in order to improve the MRS parameters and applications and improve signal processing methods. The use of the reflector, fluctuating according to the Weibull law has revealed the causes of different forms of differential distribution law of fluctuations of signal phases and amplitudes of MRS and radar sensors. Comparison of the statistical characteristics has shown that the distribution densities of phases and amplitudes of input signals of the retransmitting system are approximately two times larger than the corresponding probability densities of input signals of radar sensors. This relation can be used to estimate the type of effect that caused the fluctuation process. An explanation of the fluctuation density expansion due to double radio wave reflection by stable and fluctuating parts of the reflecting object at the forward and reverse radio wave propagation was given. It was proposed to use the extension of the differential distribution law of characteristics of signals, received by the MRS to enhance the detection of the processes that cause the reflectivity fluctuation of the monitored objects.